Internationalization and Research Productivity: “Internationalists” and “Locals” in Polish Universities - Kwiek, Marek (My University, 2014)
The internationalization of the Polish academic profession is studied in a comparative quantitative European context. Our study shows that research productivity of Polish academics (following European patterns) is strongly correlated with international collaboration: the average productivity of Polish academics involved in international collaboration (“internationalists”) is consistently higher than the rate of Polish “locals” in all academic fields. The impact of international collaboration on average productivity is much higher in Poland than in other European countries studied, with important policy implications. The relationship between international cooperation and research productivity has been widely discussed, with a general assumption that collaborative activities in research increase research productivity. But as Sooho Lee and Barry Bozeman (2005: 673) pointed out, “the benefits of collaboration are more often assumed than investigated. Do those who collaborate more tend to have more publications?”. Very much so, as we shall demonstrate in the Polish case.
Keywords: Polish higher education; Poland; productivity; research productivity; academic productivity; internationalization; internationalization in research; internationalists and locals; EUROAC project; cross-national study; academic profession; publication patterns; authorship; co-authorship; publishing; impact of internationalization; internationalization policies; European higher education; European universities; Polish universities; Polish reforms; average productivity; international cooperation; internationalists and locals; stratification in research; internationalizing research; average research output; academic profession studies; Polish academics; quantitative study; European comparative; cross-European study; research output